The stability pack and inefficiencies in fiscal policy making in EMU - Kari E. O. Alho (The Research Institute of the Finnish Economy (ETLA), 2000)
The aim of the paper is to analyse the Stability and Growth Pact of EMU in a two-country model of monetary union with rational expectations and with spillovers of macroeconomic policies between the countries. The paper concentrates on tax policy, and shows that the results on optimal policy crucially depend on whether the demand channel of taxes through aggregate demand, or the supply channel, from taxes through wage formation, dominates in the determination of the rate of inflation and the international spollovers of policy. An optimal stability pact, which corrects the inefficiencies in policy making considered here, i.e., the lack of fiscal policy myopia, is derived. Finally, an evaluation of the deterrent power of the existing Stability Pact with respect to deficit spending is derived and found to be quite small in comparison to the short-run gains related to risking the sanctions of the Pact.
Keywords: E00; E62; 330; Monetary union; stability pact; fiscal policy; coordination